Effects of total and regional fat loss on plasma CRP and IL-6 in overweight and obese, older adults with knee osteoarthritis. Issue 2 (February 2015) - Beavers, K.M.; Beavers, D.P.; Newman, J.J.; Anderson, A.M.; Loeser, R.F.; Nicklas, B.J.; Lyles, M.F.; Miller, G.D.; Mihalko, S.L.; Messier, S.P.
Summary: Objective: To describe associations between total and regional body fat mass loss and reduction of systemic levels of inflammation (C-reactive protein (CRP) and interleukin-6 (IL-6)) in obese, older adults with osteoarthritis (OA), undergoing intentional weight loss. Design: Data come from a single-blind, 18-month, randomized controlled trial in adults (age: 65.6 ± 6.2; Body mass index (BMI): 33.6 ± 3.7) with knee OA. Participants were randomized to diet-induced weight loss plus exercise (D + E; n  = 150), diet-induced weight loss-only (D; n  = 149), or exercise-only (E; n  = 151). Total body and region-specific (abdomen and thigh) fat mass were measured at baseline and 18 months. High-sensitivity CRP and IL-6 were measured at baseline, six and 18 months. Intervention effects were assessed using mixed models and associations between inflammation and adiposity were compared using logistic and mixed linear regression models. Results: Intentional total body fat mass reduction was associated with significant reductions in log-adjusted CRP ( β  = 0.06 (95% CI = 0.04, 0.08) mg/L) and IL-6 ( β  = 0.02 (95% CI = 0.01, 0.04) pg/mL). Loss of abdominal fat volume was also associated with reduced inflammation, independent of total body fat mass; although models containing measures of total adiposity yielded the best fit. The odds of achieving clinically desirable levels of CRP (<3.0 mg/L) and IL-6 (<2.5 pg/mL) were 3.8 (95% CI = 1.6, 8.9) and 2.2 (95% CI = 1.1, 4.6), respectively, with 5% total weight and fat mass loss. Conclusions: Achievement of clinically desirable levels of CRP and IL-6 more than double with intentional 5% loss of total body weight and fat mass. Global, rather than regional, measures of adiposity are better predictors of change in inflammatory burden. Clinical Trial Registration Number: NCT00381290.